Contribution to the ecological management of the seed chalcid wasp Eurytoma plotnikovi Nikol’skaya (Hymenoptera: Eurytomidae) in pistachio orchards - Lykouressis, D.; Perdikis, D.; Biba, A. (ENTOMOLOGIA HELLENICA, 2008)
Aspects related to the management of the pistachio seed wasp Eurytoma plotnikovi Nikol’skaya (Hymenoptera: Eurytomidae), were investigated. E. plotnikovi has internal feeding habits. However, the external appearance of the fruits could be used to distinguish between infested and uninfested fruits, since fruits partly blackish or brownish and shriveled had higher infestation levels than those without any discolouration. The adult emergence from the fruits was completed within a short period of 12 days, from the middle until the end of May. This pest overwinters as larva inside the mummified fruits. The application of sanitation measures for the control of this pest was experimentally investigated. The results showed that no adults emerged from fruits that were buried in the soil but also from those that remained on the soil surface during winter. Thus, it seems that there is no need for burying them by tillage under the soil as it had been proposed. This result might be essential in the wider adoption of this method in the management of this pest.